The Influence of Fluid Dynamics on Physical Uncertainties of Hydrocarbon Reservoir - Imam Setiaji Ronoatmojo; Muhammad Burhannudinnur; Yarra Sutadiwiria; Dewi Syavitri; Grace Stephani (Testing Center for Oil and Gas LEMIGAS, 2025)
Uncertainty is often present in the relationship between physical property variables and the complexity increases, when mechanical properties are included. The problems becomes more interesting in cases, where fluid dynamics act as the primary contributing factor. Pore pressure changes is the main actor of every uncertainty of physical properties. Therefore, this study aimed to examine the influence of fluid dynamics on physical uncertainties of hydrocarbon reservoir. To achieve this objective, well data from production and enhanced oil recovery (EOR) operations between 1994 to 2007 were entangled. Specifically, 3D seismic data was incorporated to distribute physical and mechanical properties after well periodization. In this study, the impact of pore pressure changes on minimum horizontal stress from 1994-2017 was also examined. The results showed that changes in porosity were not significant, but variations in bulk modulus and Poisson's ratio remained observable. Furthermore, tensors field were not dominated by vertical stress, instead of horizontal stresses. Changes in pore pressure apparently had a significant impact on minimum horizontal stress. The increase of minimum horizontal stress reached approximately one third of pore pressure change. Consequently, the stress regime transitioned from the strike-slip fault in 1994 to thrust fault in 2017, emphasizing a significant increase in the influence of horizontal stress. While water injection and oil production did not lead to significant changes in physical properties, the effects were evident in the variations of Poisson's ratio.